Analysis the Competitive Advantage Strategies of Enterprises on Organic Agriculture Productions in Luang Prabang Province - SONESAI, KHAMSONE; SIOUDOMPHAN, Soutthavone; SIPHADA, Vatthanaly; OUNPHOUVONG, Stamy; PHANTOUAMATH, Poutthalack (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to examine entrepreneurs' perspectives on the use of business competition strategies in organic agricultural production, and to analyze the effects of these strategies on the success of organic agricultural enterprises in Luang Prabang Province. The research employed a mixed-methods approach, including field data collection through observations, questionnaires, and interviews with entrepreneurs engaged in organic agriculture in the region. Regression analysis was used as the primary statistical tool. The findings revealed that respondents rated the importance of competitive strategies as follows: the differentiation strategy and cost leadership strategy were both rated at a high level on average, while the focus strategy was rated at the highest level on average. Regarding the impact of these strategies on business success, entrepreneurs perceived success factors in organic agricultural production at the highest level on average. Key success factors included increased market share, quality control and product/service development, development of employee knowledge, skills, attitudes, and relationships, efficient resource utilization to reduce costs, and the generation of long-term sales and profits. Based on regression analysis, the study found that only the cost leadership strategy significantly predicted changes in business success, with statistical significance at the 95% confidence level (t-test < 0.05). In contrast, the differentiation and focus strategies did not show a statistically significant effect (t-test > 0.05). Therefore, the cost leadership strategy can be considered a predictor of business success in organic agriculture: greater emphasis on cost leadership leads to increased success, whereas reduced emphasis may lead to decreased success.